How to Use Multimedia Whiteboard Animation for Scientific Works Companying? (Case Study in UPBJJ UT Semarang) - Sri Sumiyati; Aini Indriasih; Muhrom Ali Rozai; Mohammad Haryono (Journal of Innovation in Educational and Cultural Research, 2022)
The research objective is multimedia whiteboard animation's impact on understanding and completing the preparation of non-basic education (non-pendas) students' scientific work at UPBJJ UT Semarang. The research objects are 123 non-pendas students taking scientific work courses at UPBJJ UT Semarang, which are explored using a questionnaire. The research used a qualitative analysis of the completion of the preparation of scientific papers using the Whiteboard Animation learning media. The learning process showed the average good and very good answers of 63.41% in the high category, 68.09% in the very high category for content of learning materials, and 60.16% in the high category for the impact of Whiteboard Animation. Overall, students' perception of the Whiteboard Animation-based learning process is very effective, proven by: 1) 85 students (69.10%) uploaded their scientific work before the lecture was over, 2) the average value of students' perceptions for all indicators was high. The limitations are the difficulty of controlling respondents because the experiment was carried out by students online. The factors assessed are only learning media. To determine whether students will pass or fail, it is not the tutor in charge of this course but the students. Even though students have uploaded scientific papers, they cannot determine it.